2023
DOI: 10.21037/atm-22-4258
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia following robot-assisted thoracic surgery for mediastinal disease: retrospective comparative study of general anesthesia alone, combined with epidural analgesia, and with ultrasound-guided thoracic paraspinal block

Abstract: Background Recently, robot-assisted thoracic surgery has been increasingly performed for mediastinal disease. However, appropriate postoperative analgesic methods have not been evaluated. Methods We retrospectively studied patients who underwent robot-assisted thoracic surgery for mediastinal disease at a single university hospital between January 2019 and December 2021. Patients were performed either general anesthesia alone, general anesthesia combined with thoracic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, some studies have pointed out that thoracic paravertebral block can easily cause epidural hematoma or spinal cord injury, and excessive use of drugs can greatly harm the respiratory movement, muscle strength, and circulatory system of patients. Furthermore, this mode has many contraindications, including the use of anticoagulants, coagulopathy, or hemodynamic instability, thereby ultimately limiting its clinical application [14,15]. Ultrasound-guided erector spinae plane block can monitor the position and depth of the puncture needle in real time through ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have pointed out that thoracic paravertebral block can easily cause epidural hematoma or spinal cord injury, and excessive use of drugs can greatly harm the respiratory movement, muscle strength, and circulatory system of patients. Furthermore, this mode has many contraindications, including the use of anticoagulants, coagulopathy, or hemodynamic instability, thereby ultimately limiting its clinical application [14,15]. Ultrasound-guided erector spinae plane block can monitor the position and depth of the puncture needle in real time through ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TEA can be particularly effective for managing the pain associated with port site incisions and the dissection of the thymus gland. Moreover, Kusano et al [ 24 ] performed a retrospective study comparing the effect of general anesthesia alone, general anesthesia combined with TEA, or general anesthesia combined with ultrasound-guided thoracic blocks. Their results showed that TEA provided better analgesia after robot-assisted thoracic surgery for mediastinal disease than general anesthesia alone, as indicated by lower pain scores and fewer rescue analgesic requirements.…”
Section: Thoracic Epidural Anesthesiamentioning
confidence: 99%
“…The authors demonstrated a statically significant difference in pain scores at six and twelve hours after surgery between the NB and TEA groups, in favor of TEA (numerical rating scale 1.2±1.6 vs. 2.4±1.8 and 1.2±1.5 vs. 2.2±1.7). This finding is important but as highlighted by the authors, the clinical impact of this small difference may be questioned ( 2 ). Indeed, a statistical significance does not necessarily mean that the effect is clinically relevant.…”
mentioning
confidence: 99%
“…Postoperative pain after robot-assisted thoracic surgery (RATS) for mediastinal disease alone has not been addressed to this day. Having investigated pain after RATS for both lung resection and mediastinal disease ( 1 ), Kusano et al focused this time more specifically on mediastinal surgery ( 2 ). It is particularly helpful to be able to rely on the results of procedure-specific studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation